The Church at the Crossroads of the Times: Between Faith Tradition and Digital Innovation - Silaban, David (Hikmat : Jurnal Agama Kristen, 2024)
The advent of digital technology has brought about significant changes in various aspects of human life, including the faith life of Christians and the role of the church as a spiritual institution. On the one hand, the church is faced with the challenge of upholding centuries-old values ​​and traditions of faith. However, on the other hand, the church is also challenged to adapt to technological advances to remain relevant in a fast-paced and digital world. This study aims to examine how the church can maintain a balance between sacred faith traditions and ever-evolving digital innovations. Through theological reflection and a descriptive-qualitative approach, the study finds that church digitalization offers significant opportunities for expanding ministry, strengthening congregational communication, and reaching new believers. However, if not balanced with spiritual depth and liturgical discipline, the church risks losing the meaning of the sanctity of worship and true spiritual intimacy. The study confirms that the key to facing this crossroads of time is spiritual wisdom—the church's ability to utilize technology without sacrificing the truth of the Gospel and fidelity to the faith tradition inherited from the apostles.